21ST CENTURY EDUCATIONAL TRANSFORMATION: LITERATURE REVIEW ON INNOVATION IN THE CONTEXT OF MODERN EDUCATION - Muhibburrohman, Ohib; Fauzi, Anis; Qurtubi, Ahmad (J-MIND (Jurnal Manajemen Indonesia), 2024)
The purpose of this study is to provide a fundamental theoretical understanding of the basic concepts of innovation, as well as an understanding of the goals, forms, challenges, strategies, to the targets of innovation in education. This research uses a qualitative method with a literature study approach. Data was collected using documentation, which means searching literature on six research topics; 1). Understanding educational innovation; 2). Purpose of innovation; 3). Forms of innovation in education; 4). Challenges of educational innovation; 5). Education innovation strategy; 6). Target innovation in education. This research uses qualitative methods with a literature study approach, as well as data collected with documentation techniques. This research resulted in the result that educational innovation is needed in relation to the phenomenon of the times. In the era of the 21st century, it has a positive and negative impact on the world of education. This negative impact is an opposition for the world of education to prepare appropriate strategies to create innovations both from teachers, students, curriculum, and the goals of education itself.